An evaluation index system for regional mobile SARS-CoV-2 virus nucleic acid testing capacity in China: a modified Delphi consensus study - Dong-sheng Di; Jian-li Zhang; Mu-hong Wei; Hao-long Zhou; Yuan Cui; Ru-yi Zhang; Ye-qing Tong; Jun-an Liu; Qi Wang (BMC, 2022)
Abstract Background Large-scale detection has great potential to bring benefits for containing the COVID-19 epidemic and supporting the government in reopening economic activities. Evaluating the true regional mobile severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) virus nucleic acid testing capacity is essential to improve the overall fighting performance against this epidemic and maintain economic development. However, such a tool is not available in this issue. We aimed to establish an evaluation index system for assessing the regional mobile SARS-CoV-2 virus nucleic acid testing capacity and provide suggestions for improving the capacity level. Methods The initial version of the evaluation index system was identified based on massive literature and expert interviews. The Delphi method questionnaire was designed and 30 experts were consulted in two rounds of questionnaire to select and revise indexes at all three levels. The Analytic Hierarchy Process method was used to calculate the weight of indexes at all three levels. Results The evaluation index system for assessing the regional mobile SARS-CoV-2 virus nucleic acid testing capacity, including 5 first-level indexes, 17 second-level indexes, and 90 third-level indexes. The response rates of questionnaires delivered in the two rounds of consultation were 100 and 96.7%. Furthermore, the authority coefficient of 30 experts was 0.71. Kendall's coordination coefficient differences were statistically significant (P < 0.001). The weighted values of capacity indexes were established at all levels according to the consistency test, demonstrating that 'Personnel team construction' (0.2046) came first amongst the five first-level indexes, followed by 'Laboratory performance building and maintenance' (0.2023), 'Emergency response guarantee' (0.1989), 'Information management system for nucleic acid testing resources' (0.1982) and 'Regional mobile nucleic acid testing emergency response system construction' (0.1959). Conclusion The evaluation system for assessing the regional mobile SARS-CoV-2 virus nucleic acid testing capacity puts forward a specific, objective, and quantifiable evaluation criterion. The evaluation system can act as a tool for diversified subjects to find the weak links and loopholes. It also provides a measurable basis for authorities to improve nucleic acid testing capabilities.